(untitled) (Research, Society and Development, 2022)
Vitiligo is a relatively common disease, it is considered chronic and characterized by the appearance of white spots on the skin often caused by emotional issues. This study sought to analyze the main psychosocial impacts on the lives of individuals with vitiligo, for this, it sought to understand the main physical and psychological symptoms caused by the disease to later understand the psychosocial impacts involved and how they affect the lives of these individuals. The methodology used was an integrative literature review. For data collection, scientific articles published in the last 06 years, present on SciELO platforms, were analyzed; CAPES and PubMed. The results found with the descriptors selected in the Health Sciences Descriptors (DeCS) database were initially 7,313, after using the filters and inclusion and exclusion criteria, 13 articles were selected for full reading, 10 articles being selected. Thus, it was possible to infer from the references used linked to the area of ​​study of psychosomatics that diseases are not considered as an isolated fact in the body, but are a result of a process experienced by the individual, as is the case of vitiligo that, although it has not known origin, its causes can refer to various health problems and psychosocial issues. Therefore, it was concluded that for the most part, the psychosocial impacts on the individual are negative, causing these subjects to have a quality of life such as impaired physical, mental and social well-being, further aggravating the stains, which may trigger the development of other diseases. illnesses.